Reporte sobre la evaluación de los 20 mejores híbridos de Megathyrsus maximus previamente identificados en 2018 - Hernández, Luis Miguel; Castiblanco, Valheria (International Center for Tropical Agriculture, 2019)
To identify promising hybrids of the Megathyrsus breeding program [Megathyrsus maximus (Jacq.) B. K. Simon & S. W. L. Jacobs (= Panicum maximum Jacq.)], 20 apomitic hybrids pre-selected from a population of 80 F1 hybrids were evaluated. This F1 population comes from the cross between a sexual genotype (PM15) and 90 accessions of the CIAT germplasm bank. The evaluations were made comparing agronomic traits (such as biomass production, growth habit, height, cover, greenery and pure seed production) with commercial cultivars Mombasa (CIAT: 6962), Tanzania (CIAT: 16031), AGROSAVIA Sabanera, Megathysus Naturalized and Check1 (Witness with sexual reproduction). Currently the stablishment of the experiment was done, as well as two phenotypic evaluations. The phase of data collection will be finished during 2020 as well as data analysis and selection.